Early immunological responses to the mRNA SARS-CoV-2 vaccine in patients with neuromuscular disorders - Iwayama, Hideyuki; Ishihara, Naoko; Kawahara, Kohei; Madokoro, Yuta; Togawa, Yasuko; Muramatsu, Kanji; Murakami, Ayuka; Kuru, Satoshi; Kumagai, Toshiyuki; Ohashi, Wataru; Nanya, Kengo; Hasegawa, Shinji; et al. (Frontiers in Immunology, 2022)
Backgrounds Intramuscular injection of the SARS-CoV-2 vaccine has raised concerns about its use in patients with neuromuscular disorders (NMDs). We evaluated the response of patients with NMDs to the BNT162b2 vaccine. Methods Healthy subjects, patients with spinal muscular atrophy (SMA), and patients with Duchenne muscular dystrophy (DMD) were included. All participants received two BNT162b2 doses. SARS-CoV-2 antibody titers at baseline and 2 weeks after each vaccination were compared between groups. Residual muscle volume was evaluated in NMDs group. A questionnaire documented adverse reactions. Results Eleven patients with NMDs (9 with SMA, 2 with DMD; 7 males; aged 32.7 ± 19.3 years) and 346 healthy subjects (60 males, aged 40.0 ± 12.4 years) were included. Antibody titers (U/mL) were similar between groups (baseline: <0.40 vs. <0.40, first vaccination, 145 ± 258 vs. 103 ± 1192, and second vaccination, 1528 ± 1265 vs. 1429 ± 944; p = 1.000, 0.909, and 0.736, respectively). A negative correlation was found between antibody titers and residual muscle volume but was not significant (Mercuri scale, r = −0.429, p = 0.249; fat infiltration rate, r = −0.194, p = 0.618). The adverse reactions were comparable between groups. Conclusion The BNT162b2 vaccine is safe and effective in patients with NMDs.